2020
DOI: 10.1021/acs.jpcb.0c05108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solvent Polarity on Li-ion Diffusion in Polymer Electrolytes: An All-Atom Molecular Dynamics Study with Charge Scaling

Abstract: We herein report an all-atom molecular dynamics study on the role of solvent polarity for Li + diffusion in polymer electrolytes using PEO–LiTFSI (poly(ethylene oxide)–lithium bis(trifluoromethane)sulfonimide) as a model system. By separating the effect of T g and the effect of solvent polarity in our simulations, we show that the maximum in the diffusion coefficient of Li + with respect to the dielectric constant of polymer solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 66 publications
4
47
0
Order By: Relevance
“…Kubo conductivity σ G-K when modulating the solvent polarity as seen in Fig.1b. Both of these results support our previous observations of the effect of solvent polarity on the Li + transportation in PEO-LiTFSI systems41 and agree with other recent studies of polymer electrolyte systems 42,43. …”
supporting
confidence: 93%
“…Kubo conductivity σ G-K when modulating the solvent polarity as seen in Fig.1b. Both of these results support our previous observations of the effect of solvent polarity on the Li + transportation in PEO-LiTFSI systems41 and agree with other recent studies of polymer electrolyte systems 42,43. …”
supporting
confidence: 93%
“…70 A less used approach is to scale the point charge of solvent molecules to modulate the solvent polarity. 71,72 Thus far, we have shown that MCEs exhibit a higher diffusivity, while the EC-base and ECF electrolytes exhibit a higher ion dissociation rate and a higher ratio of ionic conducting species.…”
Section: Transport Propertiesmentioning
confidence: 93%
“…Frequency of PEO and PTHF chains visited by cations. A Na + ion is considered to have visited a chain if it coordinated with a polymer oxygen for at least 5% of simulation time (∼5 ns), as suggested by Gudla et al …”
Section: Resultsmentioning
confidence: 99%
“…The molecular dynamics package LAMMPS was used in the equilibration and production runs, with the universal forcefield PCFF+. As discussed in the previous MD studies, nonpolarizable simulation models are not recommended for ionic systems due to their overestimation of the interaction between ions. ,,,, However, polarizable models are very demanding computationally. To mitigate this issue, point charge rescaling in classical force fields has been proposed as a way to reproduce transport properties in systems containing salts and organic electrolytes .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation